2006
DOI: 10.1016/j.surfcoat.2004.10.134
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and microstructural characterization of laser-glazed plasma-sprayed thermal barrier coatings

Abstract: Laser-glazing has been revealing a high potential for the improvement of plasma-sprayed (PS) thermal barrier coatings (TBCs) by reducing surface roughness, eliminating open porosity on the surface and generating a controlled segmented crack network, although the relationship of the processing parameters with the resultant properties has not yet been completely established. In this investigation, TBCs consisting of atmospheric plasma sprayed (APS) ZrO 2 -8%wtY 2 O 3 were subjected to a CO 2 continuous wave lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 30 publications
2
49
1
1
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Laser treatment has been proved to be a highly promising method to improve the coating quality of the plasma-sprayed coatings by eliminating open pores within the coating surface and generating a controlled segmented crack network. Hot-corrosion tests in the presence of V 2 O 5 indicated that the lifetimes of the plasma-sprayed 6.1YSZ, 7.3YSZ, 12YSZ and 19.5YSZ (numbers denote wt.% of Y 2 O 3 ) coatings were largely increased In our former work, the plasma-sprayed 8YSZ coating was laser glazed and achieved remarkably improved hot-corrosion resistance against molten V 2 O 5 + Na 2 SO 4 salts.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Laser treatment has been proved to be a highly promising method to improve the coating quality of the plasma-sprayed coatings by eliminating open pores within the coating surface and generating a controlled segmented crack network. Hot-corrosion tests in the presence of V 2 O 5 indicated that the lifetimes of the plasma-sprayed 6.1YSZ, 7.3YSZ, 12YSZ and 19.5YSZ (numbers denote wt.% of Y 2 O 3 ) coatings were largely increased In our former work, the plasma-sprayed 8YSZ coating was laser glazed and achieved remarkably improved hot-corrosion resistance against molten V 2 O 5 + Na 2 SO 4 salts.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid cooling involved in this process also eliminates the residual monoclinic phase but leaves small traces of phase tЈ. 26 All of the above contribute to a better behavior during oxidation tests in the presence of molten salt at 1000°C than that achieved with sprayed condition coatings. 27 Laser glazing transforms the metastable ␥-Al 2 O 3 present in the APS coating to ␣-Al 2 O 3 .…”
Section: A Laser Glazing Of Tbcsmentioning
confidence: 99%
“…These segmented cracks were caused by the shrinkage of the molten material and by the relief of thermal-induced residual stresses during cooling. The segmented cracks in the coating surface are characteristic features of laser-re-melted ceramic materials [14][15][16][17][18][19][20][25][26][27].…”
Section: Characterizationsmentioning
confidence: 99%
“…In previous studies, a variety of methods have been conducted to seal the top coat surface, including the liquid metal impregnation, hot isostatic pressing (HIP), laser-glazing, sol-gel process, and thin chemical vapor deposition (CVD) overcoatings, to prevent the penetration of molten salts into the porous YSZ coatings [12][13][14][15][16][17][18][19][20][21][22][23]. Laser-glazing has been proved to be a highly promising method to improve the coating quality of the plasma-sprayed coating by reducing the surface roughness (Ra), eliminating open pores within the surface and generating a controlled segmented crack network.…”
Section: Introductionmentioning
confidence: 99%